Thermal performance and statistical analysis of a new bio-based insulation material produced using grain puffing technique. (22nd August 2022) - Khoukhi, Maatouk; Dar Saleh, Abeer; Mohammad, Ameera F.; Hassan, Ahmed; Abdelbaqi, Shaimaa
Highlights: Energy performance of a new bio-insulation material prepared from the rice was evaluated. The three factors of the insulation sample material—sample weight, temperature, and moisture ratio—were optimized. The optimal sample amount, temperature, and moisture level were identified by the response optimizer. The thermal conductivity of the newly developed insulation material is found to be appropriate. Abstract: As energy conservation has become a major issue, the building sector is moving towards low energy consumption and the development of bio-based thermal insulation materials contributes strongly to this approach. In countries with hot climate, like the UAE, thermal insulating materials play an important role in preventing heat gains in buildings. Various insulation materials are available in the market, including inorganic, organic (petrol-based and bio-based), combined materials, and new-technology materials, each of which suffers from harmful environmental impact and high cost. This research aims to identify the most optimal production parameters, including sample weight, temperature, and moisture ratio, for a newly developed bio-based insulation material produced using puffed rice grains. Using the response surface method (RSM) and Minitab software, 15 runs for optimizing the three individual parameters in the central composite design (CCD) were conducted. Their findings indicate that the moisture and temperature have a major effect on the thermal conductivity of the insulation material as well as the puffing ratio. The lowest thermal conductivity value (0.04971 W/mK) of the newly developed material at its natural conditions without the use of any binders or additives was found for the sample weight of 16.5 g compressed to a circular mold of 8 cm diameter, at the temperature of 263 °C, and the moisture level of 16%, which is acceptable when compared with other commercially available insulation materials such as polystyrene.